Prawilny – from sociolect to colloquial Polish - Kucharzyk, Renata (Papers in Linguistics, 2019)
The subject of the article is the functioning of the adjective prawilny in colloquial Polish. This word, which is a borrowing from the Russian language, appears in the sociolectal varieties of language (e.g. in criminal jargon, in the hip-hop sociolect, in student dialect). Today, we can observe the increasingly frequent use of this word in non-social communication of a nationwide range. The article presents the semantic development of this adjective. The basis of the analysis are, first of all, various types of texts published on the Internet.